THE IMPACT OF SOCIO-CULTURAL MODEL ON THE CHILD EDUCATION FOR ORAL HEALTH - Adam Maxim; Carmen Savin; Adriana Balan; Marinela Pasareanu; Vasilica Toma; Dana Cristiana Maxim; Ana Petcu; Veronica Serban (Romanian Society of Oral Rehabilitation, 2011)
Recognition, cultivation and granting of this right is a duty and an obligation for the adult, so that long-term results of education to be a sun for the young adult's to be. Aim. Change of the adult mentality regarding the child's oral health, thereby increasing the compliance adults in this direction. Material and methods. In the period 2008-2009 it was carried out a pilot study in Iasi area; the study was done on a total of 360 subjects, with chronological age limits 3.6 - 7.5 years. The study methods consisted in oral and dental assessment (in according with WHO criteria) and in psycho-sociological evaluation: sociological inquiry, structured interview with parents and children, questionnaire, Children's Dental Fear Picture (CDFP) and projective test of thematic draw. Results and discussions. In terms of socio-family structure it was observed mainly parental families, with a moderate upward for the age stage of 6.6 - 7.5 years. In term of behavioral aspect and of foreshadowing of structuring alternations of child's personality, in line with literature data and with results of our previous studies, we find an upward trend for the extroversion at 7.5 years old (32%) in relation with stage age 4.6 years (25%). The dynamic assessment of monitored children's emotional patterns reveals prevalence of the fearful child for the 3.6-6.5 years age stage, the prevalence of the emotionally insecure pattern for the 5.5-6.5 years age stage and the prevalence of unfearing pattern for the 7-7.5 years age stage. Conclusions. Children oral health education is an authentic dimension of human ecology as present and long-term predictability. Educational models and methods are "proactive", coparticipative and interpersonal ("peer education model") particularized and also with empathy towards child.